Analisis Perancangan Vacum Frying terhadap Produk Keripik Salak - Moh Mufti; Ichlas Wahid (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2014)
Abstract.Â Snake fruit is one of the fruits that are potentially in the village Galengdowo, wich can bear fruit throughout the year. The production of bark reaches Â± 60 ton/year. When the mango harvest season in particular bulk, the price of bark drastic decrease of Rp. 9.000,-/kg. to only Rp. 2.000,-/kg. so that farmers suffered substantial losses. With the help of the IbM team that TTG bark chips frying machine vacuum, it is possible for farmers to be able to make a flaky bark, so that the farmers can turn 180o of loss into a profit, because the selling price at between Rp. 65.000,-/kg upto Rp. 115.000,-/kg. By using the vacuum ftying machine, bark chips produced better, tasty, crisp, aroma unchanged, durable and does not change the texture color as fried at a low temperature 85oC. So that this condition will be able to increase the income of farmers barked in the village GalengdowoKeywords: snake fruit, vacuum frying, loss, profit